Comparison of normal fasting and one-hour glucose levels as predictors of future diabetes during a 34-year follow-up. (June 2013) - Strandberg, Arto Y.; Pienimäki, Tuula; Pitkälä, Kaisu H.; Tilvis, Reijo S.; Salomaa, Veikko V.; Strandberg, Timo E.
Abstract: Introduction. Early identification of those at risk of developing type 2 diabetes (T2DM) is essential. We examined how normoglycemic levels of fasting blood glucose (FBG) and 1-hour glucose predict the development of diabetes among men initially at low risk. Methods. In the Helsinki Businessmen Study (men born in 1919– 1934), 1, 145 men had normal FBG (< 5.0 mmol/L) in 1974, and 1-hour glucose values available. Multivariate, adjusted models were used to investigate how fasting and 1-hour glucose at baseline related to new-onset diabetes during a follow-up of 34 years. Results. The median FBG and 1-hour glucose values at baseline were 4.4 and 6.6 mmol/L, respectively. During follow-up, 108 men developed diabetes. The risk of incident diabetes was doubled for the highest quintile of FBG (fully adjusted relative risk (RR) 2.22, 95% confidence interval (CI) 1.10–4.50), and quadrupled for that of 1-hour glucose (RR 4.23, 95% CI 2.49–7.17). FBG could not separate the risk for those with higher levels of glucose in the range < 5.0 mmol/L, whereas 1-hour glucose discriminated the risk better at higher values. Conclusions. Higher values in the normoglycemic range for both fasting and 1-hour glucose predicted long-term incidence of diabetes in healthy middle-aged men.